Новые краснотелки юга Европейской части СССР - Шлугер, Е.Г. (Вестник зоологии, 1967)
The descriptions and drawings are presented of the 6 new for science species of the families Trombiculidae and Leeuwenhockiidae of the southern European part of the USSR: Brunehaldia taurica, Schoutedenichia pallidula, Neotrombicula alva, Neotrombicula dige-nuala, Leptotrombidium (Ericontrombidium) caucasica, Odontacarus armeniensis.